A STUDY ON ENGLISH ANIMAL IDIOMS FROM THE PERSPECTIVES OF CULTURAL METAPHOR AND THEIR TRANSLATION INTO VIETNAMESE (Journal of Foreign Language Studies, 2022)
Quite a few studies have prospectively examined English animal idioms and their translation into Vietnamese, but it is hard to find an in-depth study based on the perspective of cultural metaphor. By employing the qualitative approach, this study examines 422 selected English animal idioms, focusing on the similarities and differences found in comparison with their Vietnamese equivalents. The paper then proposes some solutions to translating these special expressions. In addition to recommending flexible application of translation strategies, the paper emphasizes that only when translators manage to decode and grasp how these special idiomatic expressions work linguistically and culturally can their appropriate translation be achieved
Keywords: animal idiom; cultural and conceptual metaphor; literal translation; cognitive linguistics